Oxide transistors produced by solution: Influence of annealing parameters on properties of the insulator - Carlos, Emanuel Abreu Antunes (2017)
Solution processing of amorphous metal oxides has been lately used as an option to implement in flexible electronics allowing to reduce the associated costs and get a better performance. However the research has focused more on semiconductor layer instead of focusing on the insulator layer that is related to the stability and performance of the devices. This work aims to evaluate amorphous aluminum oxide thin films produced using different precursor solutions and processing synthesis, and the influence of different annealing parameters on properties of the insulator layer in thin film transistors (TFTs) using different semiconductors. Optimized dielectric layer was obtained for aluminum nitrate based precursor solution using urea as fuel with 0.1 M concentration for an annealing of 30 min assisted by far ultraviolet (FUV) irradiation at a lamp distance of 5 cm. These thin films were applied in gallium−indium–zinc oxide (GIZO) TFTs as dielectric showing the best results for TFTs annealed at 180 oC with FUV irradiation: a good reproducibility with an average mobility of 17.32 ± 4.15 cm2 V−1 s−1, a subthreshold slope of 0.11 ± 0.01 V dec−1 and a turn-on voltage of - 0.12 ± 0.06 V; a low operating voltage and a good stability over 9 weeks. Finally the dielectric layer was applied in solution processed indium oxide (In2O3) TFTs at low temperatures and in flexible substrates for GIZO/AlOx TFTs annealed at 200 oC with FUV irradiation. The obtained results are equivalent to the published ones and in some cases surpassing the actual state of the art.